2010
DOI: 10.1136/adc.2009.168211
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of dipstick urinalysis in children admitted to hospital with severe malnutrition

Abstract: A urine dipstick positive for either LE or nitrites is a useful predictor of death in children admitted with SAM. Prospective studies to determine the role of untreated UTI in these deaths are needed before any treatment recommendations can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…10,11 Rare organism like Acinetobacter 1(3.7%) was also reported in this studies. Similar reports were also noted in the study by Caksen et al, and Thuo et al 8,12 As reported by Rabasa et al, antibiotic sensitivity patterns vary from one study to another. 5 In this study, microorganisms showed antibiotic sensitivity pattern in the following order: Amikacin (100%)> ciprofloxacin (81.4%)> cefotaxime (7% In this study, we did not have controls.…”
Section: Discussionsupporting
confidence: 85%
“…10,11 Rare organism like Acinetobacter 1(3.7%) was also reported in this studies. Similar reports were also noted in the study by Caksen et al, and Thuo et al 8,12 As reported by Rabasa et al, antibiotic sensitivity patterns vary from one study to another. 5 In this study, microorganisms showed antibiotic sensitivity pattern in the following order: Amikacin (100%)> ciprofloxacin (81.4%)> cefotaxime (7% In this study, we did not have controls.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of UTI in malnourished children in this study although lower than some previous reports (10,16,11,7,9,12,13) but is however higher than some other studies (6,8,14,15) (Table-VI). The wide variation in prevalence of UTI can be explained by the use of different study methods, geographical variation, as well as considerations or no considerations of study confounders.…”
Section: Discussioncontrasting
confidence: 76%
“…Rabasaet al 6 Nigeria 11% Shimeleset al 7 Ethiopia 37% Thuoet al 8 Kenya 6% Ahmed et al 9 Tanzania 20.3% Kala et al 10 South Africa 34.7% Berkowitz 11 South Africa 31% Caksenet al 12 Turkey 30% Brown et al 13 Bangladesh 30% Banapurmathet al 14 India 8% G. Gopalet al 15 India 11.34% Reed RP 16 Africa 26.1% Present Study (2017-18) Dibrugarh, Assam, India 16.67%…”
Section: Country Uti Prevalencementioning
confidence: 90%
“…A recent prospective observational study among Kenyan hospitalized SAM children showed the predictive value of a positive urine dipstick (either Leucocyte esterase or Nitrites) on mortality (29% vs. 12%, adjusted HR = 2.5) [64]. It also showed high resistances>50% of Coliforms to Cotrimoxazole and Gentamycin.…”
Section: Resultsmentioning
confidence: 99%